2007
DOI: 10.1016/j.ccr.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of the Myelopoiesis Regulator microRNA-223 by the AML1/ETO Oncoprotein

Abstract: Hematopoietic transcription factors are involved in chromosomal translocations, which generate fusion proteins contributing to leukemia pathogenesis. Analysis of patient's primary leukemia blasts revealed that those carrying the t(8;21) generating AML1/ETO, the most common acute myeloid leukemia-associated fusion protein, display low levels of a microRNA-223 (miR-223), a regulator of myelopoiesis. Here, we show that miR-223 is a direct transcriptional target of AML1/ETO. By recruiting chromatin remodeling enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
322
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(335 citation statements)
references
References 39 publications
9
322
1
2
Order By: Relevance
“…MiR-223 is deregulated in acute myeloid leukemia (14,15). We find that miR-223 is also expressed in the nervous system and we demonstrate that miR-223 controls the expression and function of GluR2 and NR2B subunits of the glutamate receptor.…”
mentioning
confidence: 75%
“…MiR-223 is deregulated in acute myeloid leukemia (14,15). We find that miR-223 is also expressed in the nervous system and we demonstrate that miR-223 controls the expression and function of GluR2 and NR2B subunits of the glutamate receptor.…”
mentioning
confidence: 75%
“…It has been reported that CpG islands within introns can act as promoters that are regulated by DNA methylation (Lyle et al, 2000). Along a 340-bp sequence (nucleotides À203 to 137) containing miR-223, DNA methylation of six CpG dinucleotides has been reported to contribute to miRNA repression (Fazi et al, 2007). Notably, miR520e is located at chromosome 19q13.42, locus spans a large, poorly characterized miRNA cluster (Li et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, changes in the methylation pattern of DNA regions coding for micro-RNAs (miRs) that modulate the expression of oncogenes or tumor suppressors have been reported (Datta et al, 2008;Huang et al, 2009;Pallasch et al, 2009). Inversely, it has been observed that oncofusion proteins can epigenetically silence miRs that are critically involved in lineage specification (Fazi et al, 2007). Altogether, these studies argue that locally altered methyl-CpG densities can result in the deregulation of multiple regulatory pathways, which are relevant for tumorigenesis.…”
Section: Current Therapeutic Paradigms To Treat Cancermentioning
confidence: 99%